The Muricidae (Gastropoda, Muricoidea) of the Miocene Paratethys Sea (Aspellinae, Ergalataxinae, Coralliophilinae, Rapaninae) - Harzhauser, Mathias; Landau, Bernard M.; Merle, Didier (Zootaxa, 2025)
We document 59 species of Aspellinae, Ergalataxinae, Coralliophilinae, Rapaninae and Muricidae incertae sedis from the Miocene of the Central Paratethys Sea. The subfamily Coralliophilinae is the most specious group among these subfamilies, comprising numerous rare and overlooked new species. Aspellinae and Rapaninae display moderate endemicity, whereas Coralliophilinae and Ergalataxinae are characterized by high endemicity. This points to a diversity hotspot, which formed in the coral reefs of the Middle Miocene Climatic Optimum. Favorable conditions during the Langhian (early/middle Badenian) are also reflected by an enormous boom in diversity and a distinct loss of species numbers with the subsequent onset of the Serravallian (late Badenian). Zoltania is introduced as new genus in Rapaninae. Aspella teter sp. nov., Favartia kovacsi sp. nov., Muricopsis hystrix sp. nov., Pazinotus aster sp. nov., Pazinotus pulcher sp. nov. (Aspellinae), Cathymorula exilissima sp. nov. (Ergalataxinae), Coralliophila acuta sp. nov., Coralliophila badensis sp. nov., Coralliophila elegantula sp. nov., Coralliophila hoplites sp. nov., Coralliophila megaglobosa sp. nov. and Coralliophila wegmuelleri sp. nov. (Coralliophilinae) are described as new species.